Identification and characterization of orthologs of AtNHX5 and AtNHX6 in Brassica napus - Ford, Brett A.; Ernest, Joanne R.; Gendall, Anthony R. (Frontiers in Plant Science, 2012)
Improving crop species by breeding for salt tolerance or introducing salt tolerant traits is one method of increasing crop yields in saline affected areas. Extensive studies of the model plant species Arabidopsis thaliana has led to the availability of substantial information regarding the function and importance of many genes involved in salt tolerance. However, the identification and characterization of A. thaliana orthologs in species such as Brassica napus (oilseed rape) can prove difficult due to the significant genomic changes that have occurred since their divergence approximately 20 million years ago (MYA). The recently released Brassica rapa genome provides an excellent resource for comparative studies of A. thaliana and the cultivated Brassica species, and facilitates the identification of Brassica species orthologs which may be of agronomic importance. Sodium hydrogen antiporter (NHX) proteins transport a sodium or potassium ion in exchange for a hydrogen ion in the other direction across a membrane. In A. thaliana there are eight members of the NHX family, designated AtNHX1-8, that can be sub-divided into three clades, based on their subcellular localization: plasma membrane (PM), intracellular class I (IC-I) and intracellular class II (IC-II). In plants, many NHX proteins are primary determinants of salt tolerance and act by transporting Na+ out of the cytosol where it would otherwise accumulate to toxic levels. Significant work has been done to determine the role of both PM and IC-I clade members in salt tolerance in a variety of plant species, but relatively little analysis has been described for the IC-II clade. Here we describe the identification of B. napus orthologs of AtNHX5 and AtNHX6, using the B. rapa genome sequence, macro- and micro-synteny analysis, comparative expression and promoter motif analysis, and highlight the value of these multiple approaches for identifying true orthologs in closely related species with multiple paralogs.